The Effect of Training and Development on Employee Productivity at PT Adhi Buana Karya Utama - Ardilah Santi; Agung Surya Dwianto (Eduvest - Journal of Universal Studies, 2026)
In the competitive construction industry, employee productivity is crucial for project success and company sustainability. PT Adhi Buana Karya Utama, a construction company established in 2017, faces challenges in maintaining optimal employee performance due to limited structured training and development programmes. The purpose of this study is to evaluate how training and development impact the productivity of PT Adhi Buana Karya Utama employees. The research was conducted through a descriptive qualitative approach, involving data collection through in-depth observation, documentation, and interviews. The four informants in this study were a director, an HRD staff member, an HSE staff member, and a project employee. Miles and Huberman's interactive model was used to perform data analysis, which includes data reduction, data presentation, and conclusion drawing. The results of the study show that employees' knowledge, skills, discipline, and confidence can be improved through training and development provided in a structured and continuous manner. This improvement has an impact on work productivity, as demonstrated by the completion of tasks more quickly, precisely, and efficiently. Therefore, training and development are important strategies for achieving company goals and increasing employee productivity.